Cis autocatalytic cleavage of glycine‐linked Zika virus NS2B‐NS3 protease constructs. Issue 16 (9th July 2019) - von Hammerstein, Franziska; Lauth, Luca M.; Hammerschmidt, Stefan; Wagner, Annika; Schirmeister, Tanja; Hellmich, Ute A.
Abstract : The flaviviral heterodimeric serine protease NS2B‐NS3, consisting of the NS3 protease domain and the NS2B co‐factor, is essential for ZIKA virus maturation and replication in cells. For in vitro studies a 'linked' construct, where a polyglycine linker connects NS2BCF and NS3pro, is often used. This construct undergoes autocatalytic cleavage. Here, we show that linked ZIKV NS2BCF ‐NS3pro is cleaved in cis in the NS2BCF exclusively at position R95 and not at the previously proposed alternate cleavage site at residue R29 in the NS3pro . Cleavage neither affects protease stability nor activity, despite some observed differences in spectroscopic behavior. This minimally modified construct may thus be useful for future structural and functional studies of the flaviviral protease, for example when testing new inhibitors. Abstract :